PENGARUH SISTEM PENGENDALIAN MANAJEMEN TERHADAP KINERJA KARYAWAN DENGAN INOVASI SEBAGAI VARABEL MODERATING (STUDI KASUS PADA USAHA JASA FOTOCOPY DAN PERCETAKAN AREA KETINTANG SURABAYA) - ANDRIAN SAPUTRO, FERIZ, PUJIONO (Jurnal Akuntansi AKUNESA, 2018)
This study aimed to determine the effect of Management Control System(MSM) on employee performance with innovations as an moderating variabelin The Photocopy and Printing Service Business Ketintang Surabaya Region.To test the emprical model, IBM SPSS Statistic 23 and Microsoft Excel 2013 was used. This research is quantitative, and the type of data is the data type of subject. The population was all of The Photocopy and Printing Service Business enterprises in the Ketintang Surabaya region. The sampel is 40 The Photocopy and Printing Service Business. Researchers chose purposive sampling, which became the sample is business/manager/employee of the business. The results of the study indicate that innovation has no significant effect on employee performance, and management control systems have a significant positive effect on employee performance and management control systems affect performance with innovation as varaibel which strengthens the relationship between the two. However, the overall conclusion illustrates that the photocopy service business feels sufficient with a management control system that can affect employee performance, while innovation is varaibel which strengthens the relationship between the two. Keywords : Management Control System, Employee Performance, Innovation